Ronald Reagan : an intellectual biography - Byrne, David T. (Potomac Books, 2018)
"In this ambitious work, David Byrne analyzes the ideas that informed Ronald Reagan's political philosophy and policies. Rather than appraising his personal and emotional life, Byrne's intellectual biography goes one step further; it establishes a rationale for the former president's motives, discussing how thinkers such as Plato and Adam Smith influenced him. Byrne points to three historical forces that shaped Reagan's political philosophy: Christian values, particularly the concept of a universal kingdom of God; America's firm belief in freedom as the greatest political value and its aversion to strong centralized governments; and the appeasement era of World War II, which stimulated Reagan's aggressive and confrontational foreign policy. Byrne's account of the fortieth president augments previous work on Reagan with a new model for understanding him. Byrne shows how Reagan took conservatism and the Republican Party in a new direction, departing from the traditional conservatism of Edmund Burke and Russell Kirk. His desire to spread a "Kingdom of Freedom" both at home and abroad changed America's political landscape forever and inspired a new conservatism that persists to this day."--Provided by publisher